Leisure-sports participants` engagement in preventive health behaviors and their experience of constraints on performing leisure activities during the COVID-19 pandemic - Kim, Y.-J.; Cho. J.-H.; Park, Y.-J. (Frontiers in Psychology, 2020)
This study aimed to analyze, among Korean leisure-sport participants, the correlation between their adoption of health-prevention behaviors and constraints on performing leisure activities during the COVID-19 pandemic. For this study, the demographic characteristics (sex, age, marital status, level of participation in leisure sports, years of participation in such sports, companions when participating in these sports, type of space used when participating in these sports, occupation, and average monthly income) of 544 leisure-sport participants (males: 46.0%, females: 54.0%; average age: 36.8 and 33.5 years, respectively), who were recruited on a nationwide basis, were examined through an online survey. Then, comparisons between groups were performed using independent t-tests, one-way analysis of variance, and multivariate analysis of variance. Females who participated in both indoor and outdoor leisure sports showed higher adoption of health-prevention behaviors than did their male counterparts, and married individuals who participated in indoor leisure sports showed higher adoption of health-prevention behaviors than single participants. Moreover, subjects who participated in both indoor and outdoor leisure sports by themselves had many interpersonal constraints overall, and the group of married individuals who participated in indoor leisure sports showed structural constraints. In conclusion, leisure-sport participants have adopted many health-prevention behaviors during the COVID-19 pandemic, but they also experience interpersonal constraints. These results indicate that, when similar pandemics occur in the future, personal and institutional efforts must be made to promote participation in leisure sports and prevent an excessive lack of social relations.